Trends in the development of methods of disposal of bark and bark-wood waste of long-term storage (review) - V. V. Volodin; A. A. Shubakov; S. O. Volodina; N. N. Shergina; R. G. Vasilov (Аграрная наука Евро-Северо-Востока, 2022)
The present review analyzes the problem of accumulation and utilization of bark and bark-wood waste from wood-working and pulp and paper industries. The methods of utilization are systematized, which differ for "fresh" bark and bark-wood waste of a long shelf life. The essence of biotechnological methods of deep biotransformation of bark-wood waste of long shelf life is described in more detail: composting with the use of mineral fertilizers, stimulation of native microflora, use of activated sludge and artificial consortia of microorganisms, creation of biotechnical systems in the body of bark dumps, solid-phase fermentation of bark-wood waste by xylotrophic fungi. Successful examples of the implementation of methods of biotransformation of bark-wood waste of long-term storage in the bark dumps of pulp and paper enterprises of the Perm Region of Rusian Federation are given. The algorithm of utilization of bark-wood waste by solid-phase fermentation with the help of xylotrophic fungi at the bark dumps of Syktyvkar woodworking plant (Republoc of Komi, Russia) is proposed in order to obtain soil-like substrates and fertilizers, fruit bodies of edible xylotrophic fungi and valuable fungal metabolites for medicine.